Desarrollo de una aplicación web progresiva para la fundación Sabia (Santuario Bienestar Animal) del cantón Latacunga - Acosta Toapanta, Cristian Alejandro (2022)
This technological proposal deals with the development of a Progressive Web Application (PWA), with the aim of improving the processes of the Animal Welfare Sanctuary Foundation (SABIA). As the main technique for data collection, the interview addressed to the administrator of the institution in question was used, obtaining the requirements to know the main needs and objectives that were reflected in modules of the website, by virtue of this a bibliographical investigation was carried out that helped structure the theoretical framework. Subsequently, the use of the agile Scrum methodology allowed the development of the project through: User Profiles, User Stories, Process Diagrams and Activity Flow models. The use of the Python programming language was considered of great importance under the development of a Backend using the Django Framework, while for the Frontend design, with the Bootstrap tool and the PostgreSQL database manager. In this way, a Progressive Web Application was obtained that is currently in production and accessible from the link https://www.sabiadogs.com/. Finally, the validation of the project was carried out under the Expert Judgment technique, for which there were two professionals in the Django development area who verified compliance with the functionalities both in consistency and reliability.